Impact of Efficiency on Sustainability of Banks: An Empirical Study of Pakistani Banks - Malik, Muhammad Sadiq; Balia, Sophee Sulong Bin; Ab Rahim, Rossazana Bt; Chaudhry, Naveed Iqbal; Munir, Waqar (Advances in Social Sciences Research Journal, 2024)
Purpose: This research aims to empirically investigate the impact of efficiency on the sustainable performance of banks in Pakistan through technical efficiency (TE), pure technical efficiency (PTE), and scale efficiency (SE). Design/Methodology/Approach: The research methodology that is adopted in this research is Census is based on the ideology of Positivism by testing an old theory with new data to draw new conclusions and new results. It uses mainly quantitative methods. This study has a novelty because a huge set of data was collected. Data Envelopment Analysis (DEA) has been used to calculate relative efficiency by using the DEA method while taking fixed assets, deposits & short-term funding, and equity as inputs, whereas net income securities and loans are outputs. Secondary data from Five years was collected for Pakistani Banks on a time series basis and analyzed using E-Views v10 to test the study’s hypothesis. Findings: The results suggest that efficiency significantly impacts the sustainable performance of banks. Pure technical efficiency has a significant impact on the sustainable performance of banks, in contrast, technical efficiency, and scale efficiency have no impact on the sustainable banks of Pakistan. Practical Implications: This paper will assist banking sector management to focus on efficiency to achieve banks' sustainability. Originality / Value: During the research process, the strands of reviewing literature show that renowned authors recommended the conduct of studies that measures the impact of efficiency on the sustainable performance of banks. This paper has a novelty in that impact of technical efficiency (TE), pure technical efficiency (PTE), and scale efficiency (SE) has also been measured on the sustainable performance of banks in one holistic unison study.